What Authentication Technology Should Be Chosen for Construction Manpower Management?. (2017) - Chin, Sangyoon; Kim, Inchie; Choi, Cheol-Ho
Abstract: The objective of this paper is to analyze the feasibility and limits of various authentication technologies such as radio frequency identification (RFID), quick response (QR) codes, and fingerprint, vein, iris, and facial recognition for manpower management and access control at construction sites. Based on the analysis of limits and features of authentication technologies, requirement analysis in construction field operations through interviews and site visits, and video study based on construction workers' actual use of the technologies, this study identified that the false rejection rate (FRR) and the processing time (PT) per person of an authentication technology are among the governing factors for making decisions to adopt an authentication technology for manpower management and access control. This study developed an equation to estimate the total process time using FRR and PT for each of the technologies, and the estimation results show that the difference in total process time can be up to 4 − 5 times larger for each technology. This can have a significant effect on the number of units to be installed at the level of about 2, 000 or more construction workers.